2015
DOI: 10.4014/jmb.1411.11022
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Reductase and Keratinase for Facile Synthesis of Protein-Coated Gold Nanoparticles

Abstract: We have synthesized gold nanoparticles (GNPs) using chicken feathers (poultry waste) and Bacillus subtilis RSE163. Disulfide reductase and keratinase produced by Bacillus subtilis during the degradation of chicken feather has been used to reduce Au(3+) from HAuCl4 precursor to produce gold nanoparticles. The synthesized biogenic GNPs were characterized by UV-visible spectroscopy, transmission electron microscopy (TEM), and zeta potential measurements. Fourier transform infrared (FTIR) spectroscopy indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 47 publications
1
14
0
1
Order By: Relevance
“…The results indicate that the reductase enzyme responsible for the reduction of metal ions is NADPH-dependent. NADPH is a cofactor for this biological transformation 22. Our reports are also correlated with Kumar et al (2007) who reported the reduction of gold ions to gold nanoparticles by α-NADPH-dependent sulfite reductase and phytochelatin 23.…”
Section: Resultssupporting
confidence: 89%
“…The results indicate that the reductase enzyme responsible for the reduction of metal ions is NADPH-dependent. NADPH is a cofactor for this biological transformation 22. Our reports are also correlated with Kumar et al (2007) who reported the reduction of gold ions to gold nanoparticles by α-NADPH-dependent sulfite reductase and phytochelatin 23.…”
Section: Resultssupporting
confidence: 89%
“…Bacterial ability in degrading feather was associated with two enzymes, serine protease and disulphide reductase as showed by Stenotrophomonas sp. D-1 5,17,18 . As far as we know, no report of A. chroococcum was as keratinolytic bacteria.…”
Section: Results and Discussion Chicken Feather Degradation By Azotobmentioning
confidence: 99%
“…Psoriasis lesions are noticeably thickened and thinned epidermis with heterogeneity in the skin morphology leads to variability in drug permeation and their systemic absorption [6]. We are working on the Bacillus subtilis keratinase since last 6 years and found promising hydrolyzing proficiency towards keratin which would be a subject of substantial scientific interest towards psoriasis treatment [2,7]. Present study demonstrated the expression of ker gene in E. coli and in silico binding affinities of deduced protein with psoriasis topical drugs using docking studies.…”
Section: Introductionmentioning
confidence: 86%
“…The keratinolytic activity of strain was determined by using the cell free extract of feather media as per the protocol published in our previous paper [7].…”
Section: Assay Of Keratinolytic Activitymentioning
confidence: 99%